2008
DOI: 10.1120/jacmp.v9i4.2766
|View full text |Cite
|
Sign up to set email alerts
|

A technique for reducing patient setup uncertainties by aligning and verifying daily positioning of a moving tumor using implanted fiducials

Abstract: This study aimed to validate and implement a methodology in which fiducials implanted in the periphery of lung tumors can be used to reduce uncertainties in tumor location.Alignment software that matches marker positions on two‐dimensional (2D) kilovoltage portal images to positions on three‐dimensional (3D) computed tomography data sets was validated using static and moving phantoms. This software also was used to reduce uncertainties in tumor location in a patient with fiducials implanted in the periphery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Treatment using methods designed to mitigate the effects of respiratory motion (breath hold or gating) with setup based on landmarks other than the actual tumor position requires margins of 0.7 to 0.8 cm. Two possible methods of mitigating systematic uncertainty would be either to set the patient up under image guidance based on cone-beam CT imaging of the tumor or kilovoltage imaging of implanted fiducials (16) or to acquire multiple CT data sets for treatment planning and base the treatment portal on a mean tumor location. The magnitude of setup uncertainty appears to be weakly correlated with the magnitude of GTV excursion, although this correlation may not necessarily be significant, nor does it appear predictive.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment using methods designed to mitigate the effects of respiratory motion (breath hold or gating) with setup based on landmarks other than the actual tumor position requires margins of 0.7 to 0.8 cm. Two possible methods of mitigating systematic uncertainty would be either to set the patient up under image guidance based on cone-beam CT imaging of the tumor or kilovoltage imaging of implanted fiducials (16) or to acquire multiple CT data sets for treatment planning and base the treatment portal on a mean tumor location. The magnitude of setup uncertainty appears to be weakly correlated with the magnitude of GTV excursion, although this correlation may not necessarily be significant, nor does it appear predictive.…”
Section: Discussionmentioning
confidence: 99%
“…Daily CT scan localization is utilized when more precise localization is necessary (e.g., tumors adjacent to the spinal cord), when the size of the tumor is rapidly changing, or when bony landmarks are not representative of internal anatomy. Prior studies have shown that with daily kV imaging, interfractional variation is approximately 5 mm (Nelson et al 2008 ) and, with CBCT, can be reduced to approximately 3 mm. These are thus the margins that are utilized at our institution (Borst et al 2007 ).…”
Section: Simulation and Daily Localizationmentioning
confidence: 98%
“…The authors found that systematic and random uncertainties ranged between 4 and 6 mm in all three directions [ 22 ]. With daily portal imaging, the authors found in a subsequent study that alignment based on implanted fiducials reduced systematic errors in the left-right and superior-inferior direction each by 3 mm [ 23 ]. As a result, daily portal imaging is often utilized to decrease setup error in conventionally fractionated regimens, with a daily setup error of up to 5 mm.…”
Section: The Role Of Adaptive Radiotherapy In Intrafraction Adaptimentioning
confidence: 99%